Child Sport Concussion Assessment Tool 5th Edition: Normative Reference Values in Demographically Diverse Youth. Issue 2 (March 2022) - Kelshaw, Patricia M.; Cook, Nathan E.; Terry, Douglas P.; Iverson, Grant L.; Caswell, Shane V.
Abstract : Objectives: Examine sociodemographic differences (gender, age, and language spoken at home) on baseline Child Sport Concussion Assessment Tool 5th Edition (Child SCAT5) scores and establish normative reference data for the Child SCAT5 among middle school student athletes. Design: Cross-sectional study. Setting: Nine middle schools in Virginia. Participants: A sample of 1355 athletes playing competitive school-sponsored sports (ages 11-13, M = 12.3 ± 0.8; 40.1% girls, 59.9% boys) during the 2017 and 2018 school year. Certified athletic trainers administered the Child SCAT5 within the first 2 weeks of the sport season. Independent Variables: Self-reported gender, age, and language spoken at home. Main Outcome Measures: All Child SCAT5 outcome measures. Results: Gender, age, and language spoken at home were associated with Child SCAT5 scores, but the magnitude of differences was generally small. Specifically, girls endorsed more symptoms (girls: M = 8.4 ± 5.7, boys: M = 7.5 ± 5.7; P = 0.003) and greater symptom severity (girls: M = 11.6 ± 9.4, boys: M = 10.4 ± 9.3; P = 0.006) than boys and performed slightly better than boys on cognitive and balance tasks. Older students performed slightly better than younger students on tests of cognition (eg, SAC-C: 11-year-olds: M = 21.3 ± 2.1, 13-year-olds: M = 21.7 ± 2.1; P = 0.02). Total symptoms ( P = 0.01), symptom severity ( P = 0.01), immediate memory ( P < 0.001), delayed recall ( P = 0.001), and SAC-C total scores ( P = 0.002) differed across language groups. Conclusions: Gender, age, and language spoken in the home are associated with baseline scores on multiple components of the Child SCAT5 among middle school students, although the magnitudes of observed differences are small. Normative reference values are provided for clinicians when interpreting Child SCAT5 scores.